On the tenures and taxation of India - Murphy, Joseph John (Dublin Statistical Society, 1858)
The government, in the greater part of India, being the sole landowner, and almost sole capitalist, is under the obligation of attending to many things which in Europe may be safely left to private enterprise. Public works, especially works of irrigation, have of late years been prosecuted with great vigour by the Indian government, and with the happiest results, both to the revenue of the state and the condition of the people. But one of the most important results of modern and Christian civilization is to narrow the functions of the government, and when the transfer of the land of India as property from the government to the cultivators has been fully effected, it will probably be time for the government to abandon to private enterprise the function of constructing and managing the great public works.
Read Monday, 15th March, 1858
Keywords: India, Land tenure; India, Taxation; 314.15